Overexpression of miR-149 attenuates opioid-related perturbations in neural stem cell fates and serves as a translational biomarker for infants with prenatal opioid exposure - Rhea E. Sullivan; Claire J. Miller; Quinn Ahrens; Brittany J. Fronheiser; Fumiyuki C. Gardner; Emma Raich; Sara Mills-Huffnagle; Christiana Oji-Mmuo; Steven D. Hicks (PLoS ONE, 2026)
There is currently no biomarker to predict the maximum morphine dose (MMD) for newborns experiencing withdrawal from chronic prenatal opioid exposure (POE). This is due, in part, to a lack of understanding about how the developing brain is altered by chronic opioid exposure and withdrawal on a molecular level. We previously developed a human induced pluripotent stem cell-derived model of POE and withdrawal to examine the impact on neural progenitor cell fates. Here, we leveraged our model to investigate the role of two microRNAs implicated in both neural stem cell differentiation and opioid signaling: miR-149 and miR-23b. Further, we asked if these microRNAs were related to the need for morphine treatment and MMD in the saliva of infants with POE. Levels of miR-149 (One-way ANOVA, F = 34.18, p < 0.0001), but not miR-23b (One-way ANOVA, p = 0.14), were significantly decreased in human neural progenitors after chronic morphine exposure (Tukey’s, adj. p = 0.004), and decreased further in those that underwent withdrawal compared to vehicle exposed controls (Tukey’s, adj. p < 0.0001). The relevance of miR-149 to neonates experiencing withdrawal after POE was confirmed by decreased salivary levels of miR-149 compared to levels in healthy infants 24–96 hours after birth (n = 56, 28 unexposed and 28 infants with POE) (Mann-Whitney U, p < 0.0001). Stratifying infants with POE by need for pharmacotherapy revealed a further decrease in levels of miR-149 in infants that required treatment (One-way ANOVA, p < 0.0001). In a hierarchical linear regression model utilizing infant demographic factors, addition of miR-149 levels in neonatal saliva improved performance for predicting the MMD necessary for symptom control (R = 0.673, p = 0.002). These results indicate the potential relevance of miR-149 levels in infants with prenatal opioid exposure. Validation in larger cohorts is necessary.